Membrane Binding and Subcellular Localization of Retroviral Gag Proteins Are Differentially Regulated by MA Interactions with Phosphatidylinositol-(4,5)-Bisphosphate and RNA - Jingga Inlora (American Society for Microbiology, 2014)
ABSTRACT The matrix (MA) domain of HIV-1 mediates proper Gag localization and membrane binding via interaction with a plasma-membrane (PM)-specific acidic phospholipid, phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P2]. HIV-1 MA also interacts with RNA, which prevents Gag from binding to membranes containing phosphatidylserine, a prevalent cellular acidic phospholipid. These results suggest that the MA-bound RNA promotes PM-specific localization of HIV-1 Gag by blocking nonspecific interactions with cellular membranes that do not contain PI(4,5)P2. To examine whether PI(4,5)P2 dependence and RNA-mediated inhibition collectively determine MA phenotypes across a broad range of retroviruses and elucidate the significance of their interrelationships, we compared a panel of Gag-leucine zipper constructs (GagLZ) containing MA of different retroviruses. We found that in vitro membrane binding of GagLZ via HIV-1 MA and Rous sarcoma virus (RSV) MA is both PI(4,5)P2 dependent and susceptible to RNA-mediated inhibition. The PM-specific localization and virus-like particle (VLP) release of these GagLZ proteins are severely impaired by overexpression of a PI(4,5)P2-depleting enzyme, polyphosphoinositide 5-phosphatase IV (5ptaseIV). In contrast, membrane binding of GagLZ constructs that contain human T-lymphotropic virus type 1 (HTLV-1) MA, murine leukemia virus (MLV) MA, and human endogenous retrovirus K (HERV-K) MA is PI(4,5)P2 independent and not blocked by RNA. The PM localization and VLP release of these GagLZ chimeras were much less sensitive to 5ptaseIV expression. Notably, single amino acid substitutions that confer a large basic patch rendered HTLV-1 MA susceptible to the RNA-mediated block, suggesting that RNA readily blocks MA containing a large basic patch, such as HIV-1 and RSV MA. Further analyses of these MA mutants suggest a possibility that HIV-1 and RSV MA acquired PI(4,5)P2 dependence to alleviate the membrane binding block imposed by RNA. IMPORTANCE MA basic residues in the HIV-1 structural protein Gag interact with phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P2] and RNA. RNA inhibits HIV-1 MA binding to non-PI(4,5)P2 acidic lipids. This inhibition may promote PM specificity of Gag membrane binding, an early essential step in virus assembly. However, whether and how relationships between these interactions have developed among retroviruses are poorly understood. In this study, by comparing diverse retroviral MA domains, we elucidated a strong correlation among PI(4,5)P2 dependence, susceptibility to RNA-mediated inhibition, and cellular behaviors of Gag. Mutagenesis analyses suggest that a large basic patch on MA is sufficient to confer susceptibility to RNA-mediated inhibition but not for PI(4,5)P2-dependent membrane binding. Our findings highlight RNA’s role as a general blocker of large basic patches and suggest a possibility that some retroviruses, including HIV-1, have evolved to bind PI(4,5)P2, while others have adopted smaller basic patches on their MA domains, to overcome the RNA-mediated restriction of membrane binding.